SOME FEATURES OF IMPROVING THE QUALITY OF EDUCATION IN TEACHING OF FOREIGN LANGUAGES (American Journal of Pedagogical and Educational Research, 2023)
This article discusses some peculiarities of improving the quality of education in teaching foreign languages. Attention is paid to improving the effectiveness of training sessions, through the use of various audio and video materials,with the help of computer technology. The possibilities of the technology of individualized learning, which contributes to increasing the level of foreign languageproficiency, are discussed.